Effect of opening architectural shapes on users' emotion with Kansei method. (3rd April 2018) - Bagheri, Mahsa; Shahroudi, AbasAli
ABSTRACT: Paying attention to psychological aspect of human being along with meeting his physical needs are among the factors that have found their special place in different sciences such as architectural design. Appropriate design of interior space and facade of spaces will lead to stimulation of positive feelings. However, architects consider it with their personal tendencies and tastes. The aim of the present study is to assess and extract user's emotions about facade openings of Maskan (Housing) Bank in the city of Sari, Iran. Investigations were conducted through the Kansei engineering method to calculate and obtain the user's feeling accurately. Questionnaires were set for 200 statistical samples through the semantic differential (SD) method with a 7-point Likert scale. The responses were analyzed in the SPSS software with a mean test, standard deviation, independent sample T -test, one-way ANOVA and Pearson correlation. Findings indicate that participant's background characteristics such as gender, age, temperament, blood group, education and work had effects on users' emotions. This research also approves a significant relation between design quantitative (type of openings) and qualitative (Kansei words) characteristics in the Kansei engineering technique. The emotion of most of the participants toward picture 2 (triangular openings) was assessed inappropriate. The arched openings in the traits related to religion in words such as loyal, trustee, and moderate with a correlation of 0.6, 0.63, and 0.6, respectively; and rectangular openings with vertical extension in traits related to finance and banking in words such as stability with the correlation of 0.62 had the maximum significant relationship.